Ugliness in the lyric poetry of Gottfried Benn – outline of a doctoral dissertation (Free your mind: Reflections on language, literature and culture, 2022)
The motive of ugliness in the lyric poetry of Gottfried Benn is an integral element of his work, whereas research concentrates mainly on ideological views as well as professional medical experience of the German author. These issues undoubtedly have influence on Benn’s poetry, however, the aesthetics of ugliness, which is a key element here, appears to be treated secondarily. The aim of this article is to present the motive of ugliness in the lyric poetry of the author as well as present the current status of research on this subject. Academicism of the motive of ugliness dates back to ancient times, when the crucial point for Greek philosophers and thinkers was to try to define beauty and its opposite – ugliness. The aesthetic category of ugliness in literature is presented as the opposite to beauty, innocence and good. It is often compared to evil, demons and human tragedies. Although the aesthetic category of ugliness was especially common in modernism, it must be mentioned that it was also present previously.